Gastric Adenocarcinoma Missed at the Incisura Angularis During Initial Endoscopy: A Case Report. - Attieh, Philippe; Derbas, Bassem; El Mustapha, Wael; Karam, Karam; Fiani, Elias (Clinical Medicine Insights: Case Reports, 2026)
Background: Gastric adenocarcinoma remains a major cause of cancer-related morbidity and mortality worldwide. Early detection is crucial for improving prognosis; however, early lesions may be overlooked during esophagogastroduodenoscopy (EGD), particularly in anatomically challenging areas such as the incisura angularis. This region is considered a high-risk site for gastric neoplasia and may act as a blind spot during routine endoscopic evaluation. Case summary: A 38-year-old female with a history of chronic gastroesophageal reflux disease presented with worsening reflux symptoms, postprandial epigastric pain, and recurrent vomiting. Nine months prior, the patient had undergone an EGD for similar symptoms, which showed no significant abnormalities. Despite treatment with proton pump inhibitors, her symptoms progressively worsened and were accompanied by early satiety and an 8-kg unintentional weight loss. A repeat EGD was performed and revealed suspicious ulcerative lesions at the level of the incisura angularis. Multiple biopsies were obtained, and histopathological examination confirmed gastric adenocarcinoma. The patient was subsequently referred for multidisciplinary management and oncological evaluation. Conclusion: This case highlights the potential for gastric adenocarcinoma to be missed during initial endoscopic examination, particularly at the incisura angularis. Careful mucosal inspection and appropriate retroflexion during EGD are essential for improving lesion detection in this high-risk anatomical region.